Diagnostically significant changes in subsets CD11b+CD64-CD32+CD16+, CD11b+CD64+CD32+CD16+ neutrophilic granulocytes of immunocompromised women with chronic infectious and inflammatory diseases of the genital tract of various etiologies - S. V. Kovaleva; I. V. Nesterova; S. N. Pikturno; E. I. Dydyshko; N. S. Prosolypova; А. M. Chulkova (Медицинская иммунология)
Chronic pelvic inflammatory disease (PID) in women remains a problem due to the importance of medical consequences. The study of the receptor apparatus of neutrophilic granulocytes (NG) involved in anti-infective protection in diseases of various etiologies seems to be relevant. Aim: to clarify the features of variants of quantitative and phenotypic changes in subsets of NG CD11b+CD64-CD32+CD16+, CD11b+CD64+CD32+CD16+ of immunocompromised women during exacerbation of chronic PID of various etiologies. We were tested women 20-40 years: Study Group 1 (SG1, n = 20) – chronic PID during the exacerbation with mono- or mixed latent/recurrent various viral infections (chronic herpes-virus infections, papillomavirus infection, recurrent ARVI); Study Group 2 (SG2, n = 30) – chronic PID of bacterial etiologies; Comparison Group (CG)– 20 healthy women. The number of subsets CD11b+CD64-CD32+CD16+NG (major) and CD11b+CD64+CD32+CD16+NG (minor), receptor expression density (MFI) was determined (FC500, USA). It was found that in PID during the period of exacerbation, diagnostically significant differences in the subset composition of NG were revealed. We got a decrease in the CD11b+СD64-СD32+СD16+NG subset and in 7,6 times increase in the CD11b+CD64+CD32+CD16+NG subset in SG2 with chronic PID of bacterial etiology, in contrast to chronic PID occurring in combination with recurrent/persistent viral infection SG1. Negative transformation of NG subsets is associated with a predominant decrease in the level of expression of the activation CD16. The absence of an adequate response to the infectious and inflammatory process was revealed – the absence of an increase in the expression of the activation CD11b in the major subset in SG1, as well as in the minor subset in groups SG1 and SG2. In the major subset of NG in groups SG2 a decrease in the expression of the activation marker CD11b. In the various viral infections and PID (SG1), in the negatively altered minor subset of NG we got a decrease of expression of CD16, an increase of expression of CD64 and CD32. Determination of subsets of CD11b+СD64-СD32+СD16+, CD11b+CD64+CD32+CD16+NG and their phenotype can be used as diagnostic markers for the differential diagnosis of PID of viral and bacterial etiology, and for the development of new methods of targeted immunomodulatory therapy.